Equinococosis vertebral - Venegas, Luis (2019)
A 14 year-old male patient was admitted to the hospital with lower back pain, paraparesis and loss of sphincter control. The findings of the vertebral CT and MRI showed cystic tumors in the lumbosacral region with paravertebral lesions so he underwent to neurosurgery: laminectomy, cystectomy and vertebral fixation. The final diagnosis was equinococcosis.